Two-component polyurethane adhesive for lamination
By using a specific component ratio and double -component polyurethane layer pressure binder, the problem of high PAA in the composite membrane is solved, the rapid cross -linking and high internal agglomeration are realized, the storage time is reduced, and the storage time is improved, the storage time is improved, the storage time is improved, the storage time is improved, the storage time is improved, the storage time is improved, the storage time is improved, the storage time is improved, and the storage time is reduced. Has industrial productivity.
Patent Information
- Application Number
- CN201880089813.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-12-19
- Filing Date
- 2018-12-10
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2038-12-10
AI Technical Summary
After use, the existing solvent-free two-component polyurethane type laminated adhesive is used, and the amount of aromatic primary amine (PAA) extracted from the composite film is relatively high, resulting in a longer storage time and affecting industrial productivity.
Polyurethane pre-polymer A1 containing at least two-NCO-end groups A1 and at least two-OH-end-based polyurethane prefabrication B1 dual-component polyurethane layer compression adhesive compositions, through specific agglomeration reactions and The proportion of components, control -NCO / -OH Moore's equivalent ratio between 1.5 and 1.7, ensure the appropriate viscosity and cross -linking performance of the adhesive in the compressor.
A significant reduction of the extraction of PAA in the composite film, reducing it to less than 5ppb the next day, reducing the storage time of the composite film roll, increasing industrial productivity, and ensuring the internal agglomeration of the composite film. It is suitable for metal Or metallic support.
Abstract
Description
[0001] The subject of the invention is a solvent-free two-component polyurethane adhesive composition which is suitable for laminating thin layers of materials, in particular polymeric and / or metallic materials. The invention also relates to a multilayer film comprising at least two thin layers of said materials bonded together by said crosslinked adhesive composition, and to the use of said system for producing flexible packaging.
[0002] Flexible packaging used to package the most diverse products, such as those produced in the food processing, cosmetics or detergent industries, usually consists of several thin layers (in the form of sheets of film) with a thickness between 5 and 150µm and composed of various materials, such as paper, metals (such as aluminum) or thermoplastic polymers. The corresponding composite (or multilayer) films can have a thickness between 20 and 400µm and can combine the properties of the individual layers of material (also called "support") to offer the consumer a set of properties suitable for the final flexible packaging, such as, for example:
[0003] - its visual appearance (in particular the visual appearance of printed elements presenting information relating to the packaged product and intended for the consumer),
[0004] - barrier effect against atmospheric moisture or gases (especially oxygen),
[0005] - contact with foodstuffs without risk of toxicity or alteration of the organoleptic properties of the packaged food,
[0006] - Chemical resistance for certain products (e.g. ketchup or liquid soap),
[0007] - Good performance at high temperatures, such as in the case of pasteurization.
[0008] To form the final package, the multilayer film is formed by heat sealing, usually at a temperature of about 120 to 250° C., the latter technique also being used to close the package around the product for the consumer.
[0009] In industrial lamination processes, the various material layers that make up the multilayer film are combined or assembled by lamination.
[0010] These methods use adhesives (or glues) and equipment (or machines) designed for this purpose. The multilayer films thus obtained are themselves often referred to as "laminates".
[0011] These methods firstly comprise a step of applying an adhesive onto a first material film, which step consists of depositing a continuous adhesive layer having a controlled thickness, generally less than 10 μm, corresponding to a likewise controlled pressure, generally not exceeding 10 g / m 2This coating step is followed by a step of laminating a second film of material identical or different to the first layer, consisting of applying this second film under pressure to the first film covered with the adhesive layer.
[0012] Thus, composite films are finally obtained in very large width formats and are usually packaged by winding into wide reels of 1 m diameter, which can be as wide as the film can be stored, up to 2 m. These wide reels can be stored or transported, for the purpose of their use, either directly by the food processing industry, for the purpose of packaging its products, or can be cut by converters (or laminators) to reduce their width and shape to produce bags for storage and transportation, which themselves are used to package products, for example, in the food industry.
[0013] Solvent-free, two-component, polyurethane-based laminating adhesives are widely used as glues for the production of multilayer systems in the field of flexible packaging. In fact, these adhesives, which contain neither organic solvents nor water, have the advantage of being able to be used in industrial laminating operations at very high line speeds. This is precisely due to the fact that there are no organic solvents or water to be removed, thus avoiding an additional removal step of passing the laminate through an oven or any other means.
[0014] To carry out the lamination process, a solvent-free two-component polyurethane-based laminating adhesive is provided to a laminator in the form of two compositions (or components).
[0015] - a chemical containing an isocyanate end group (called the -NCO component), and
[0016] -The other contains a chemical with a hydroxyl end group (called the -OH component).
[0017] The mixing of these two components is carried out under hot conditions, by the operator of the laminating machine, at a temperature between 30 and 80 ° C (before starting), which allows correct mixing machine operation due to the appropriate viscosity.
[0018] In conclusion to the coating and lamination process of the mixture thus obtained, the isocyanate groups of the -NCO component form, with the hydroxyl groups of the -OH component, a polyurethane in the form of a three-dimensional network containing urethane groups, according to a reaction known as crosslinking, providing the cohesion of the adhesive seal between the two thin lamination layers. A suitable time to complete this crosslinking reaction and thus ensure the desired level of cohesion, which varies according to the subsequent treatment, is generally from 1 to 10 days.
[0019] Composite films produced according to this type of process are very suitable for producing composite films for flexible (or soft) packaging due to their excellent level of cohesion.
[0020] The chemicals present in the -OH component are usually polymeric or non-polymeric compounds, sometimes of natural origin (e.g. castor oil), and usually include polymers of the polyether polyol and / or polyester polyol type with a molar mass of 400 to 4000 g / mol.
[0021] The chemical species present in the -NCO component are generally polymer compounds known as prepolymers, as they are the precursors to the final crosslinked polyurethane of the adhesive sealant. These prepolymers containing -NCO end groups are generally themselves polyurethanes prepared by the polyaddition reaction of a molar excess of diisocyanate monomers (which are generally aromatic) with polyether polyols and / or polyester polyols.
[0022] However, due to the specificity of this polyaddition reaction and due to the presence of a molar excess of diisocyanate, a certain amount of unreacted diisocyanate monomers remains in the resulting -NCO component. These residual amounts of low molecular weight ("free") diisocyanate monomers are able to migrate through the multilayer film after use of the two-component adhesive and thus through the final flexible packaging. Thus, said compounds can hydrolyze by contact with water or moisture present in food or other packaged products to form primary aromatic amines (PAAs), which are considered to be very harmful to human health and the environment.
[0023] Immediately after an industrial operation for producing a composite film, the amount of PAA that can be extracted from the film is generally very high. This amount decreases over time, since the crosslinking reaction continues and is then completed within the adhesive layer of the film, which has the effect of reducing the residual amount of free diisocyanate monomers and their mobility in the composite film and therefore reducing the possibility of their migration out of the aforementioned film.
[0024] Therefore, in order to comply with the mandatory obligations, lamination manufacturers must in practice store rolls of laminated composites as long as the amount of PAA that can be extracted from the composite is above 10 ppb, or even above 5 ppb. Storage times of up to 14 days or more may be necessary before the composite film can be used to produce flexible packaging for food.
[0025] Therefore, in order to improve industrial productivity, it is highly desirable to accelerate the reduction of the amount of extractable PAA.
[0026] Prior art documents that address problems associated with PAA are known.
[0027] Thus, PCT application WO 2013 / 043652 describes a layered structure comprising at least 2 layers, one of which is formed of a composition comprising a polyurethane, as an adhesive layer, and the other, as a support, is formed of a composition comprising a polymer functionalized with acid, anhydride or amine groups capable of trapping free diisocyanate monomers. However, the support used is very specific.
[0028] International application WO2016 / 142513 discloses a polyurethane prepolymer containing -NCO end groups, which has a low monomer content and can be used as the -NCO component of a two-component polyurethane adhesive. The prepolymer is obtained by reacting a polyol with an excess of polyisocyanate and then reacting the reaction product with a compound having an acidic hydrogen H functional group that reacts with the -NCO group. However, the exemplified prepolymer is a solvent-based adhesive.
[0029] Patent US 9 458 363 describes a polyurethane adhesive composition comprising a prepolymer obtained from a polyol and a polyisocyanate containing -NCO end groups, and a compound having a molecular weight of less than 2000 g / mol and having a functional group reactive with a primary amine group. However, the adhesive compositions described in this patent are all solvent-based.
[0030] International application WO 2012 / 142148 describes an adhesive laminating composition whose -NCO component is a polyurethane prepolymer containing isocyanate end groups obtained from modified diphenylmethane diisocyanate.
[0031] However, there is always a desire to enrich the technological solutions offered to lamination manufacturers.
[0032] It was therefore an object of the present invention to provide a solvent-free, two-component, polyurethane-based laminating adhesive which, from the moment of use in a lamination process, exhibits an improved reduction over time in the amount of PAA extracted from the composite film obtained by said process.
[0033] Another object of the present invention is to provide a solvent-free two-component polyurethane type laminating adhesive having -NCO and -OH components each having a viscosity suitable for using them in a laminator after mixing the resulting composition.
[0034] Another object of the present invention is to provide a solvent-free, two-component, polyurethane-based laminating adhesive which is polyvalent in the sense that it can be adapted to supports commonly used in laminating machines.
[0035] Another object of the present invention is to provide a solvent-free, two-component, polyurethane-based laminating adhesive which, after lamination, and in particular after lamination to a metal or metallized support, gives rise to a composite film having the desired cohesive properties.
[0036] Another object of the present invention is to provide a solvent-free, two-component, polyurethane-based laminating adhesive which, after lamination, leads to a cohesive complex film after a relatively short crosslinking time.
[0037] It has now been found that these objects can be achieved in whole or in part by the adhesive composition described below.
[0038] The subject of the present invention is therefore a two-component polyurethane-based adhesive composition comprising an —NCO component and an —OH component, such that:
[0039] The NCO component is a composition A comprising a polyurethane prepolymer A1 having at least two -NCO terminal groups, A1 being obtained by a polyaddition reaction between:
[0040] - a composition A1.C1 comprising at least 35% by weight of 4,4'-elastomeric diphenylmethane diisocyanate (MDI), said percentage being expressed based on the total weight of said composition, and
[0041] - a composition A1.C2 of polyols comprising a polyether diol PE having a molar mass Mn of 800 to 1200 g / mol A 1 and polyether triol PE with a molar mass Mn of 350 to 550 g / mol A 2 , whose amount corresponds to PE A 2 / (PE A 1 + PE A 2 ) in a weight / weight ratio of 15% to 30%,
[0042] - A1.C1 and A1.C2 are used in an amount such that the -NCO / -OH molar equivalent ratio is between 2.5 and 6.5;
[0043] The OH component is a composition B comprising a polyurethane prepolymer B1 having at least two -OH terminal groups, B1 being obtained by a polyaddition reaction between:
[0044] - a composition B1.C1 comprising at least 35% by weight of 4,4'-elastomeric diphenylmethane diisocyanate (MDI), said percentage being expressed based on the total weight of said composition, and
[0045] - Composition B1.C2 of polyols with a functionality of 2, comprising, based on the total weight of the composition:
[0046] - 38 to 42% by weight of a composition B1.C2.D comprising an aliphatic polyester diol PES having a molar mass Mn of 800 to 1200 g / mol B 1 and partially aromatic polyester diols PES having a molar mass Mn of 1000 to 1400 g / mol B 2 , whose amount corresponds to PES B 1 / PES B 2 A weight / weight ratio between 0.35 and 0.45; and
[0047] -58 to 62% by weight of aliphatic polyether diols PE having a molar mass Mn of 350 to 550 g / mol B ;
[0048] -B1C1 and B1C2 are used in amounts such that the -NCO / -OH molar equivalent ratio is between 0.05 and 0.50;
[0049] - It is also provided that the amounts of -NCO and -OH components of the two-component adhesive composition should be such that the -NCO / -OH molar equivalent ratio is in the range of 1.5 to 1.7.
[0050] It has now been found that the two-component adhesive composition according to the invention makes it possible to obtain composite films having a reduced crosslinking time, whose extractable PAA content is advantageously reduced to below 5 ppb from the second day of its production, which therefore allows laminators to reduce the storage time of their composite film rolls and thus their finished product stocks. Furthermore, the film has a perfectly adequate cohesion and an excellent cohesion even in the case where one of the supports of the film is a metallized support such as, for example, metallized PET.
[0051] For composite films, these properties can be easily achieved by using a corresponding two-component adhesive composition, either by easily introducing the -NCO and -OH components into the laminator by means of a pump, due to the viscosity properties of the components, or further considering the use of the composition obtained by mixing the components in the laminator itself, also due to the suitable viscosity curve of the composite.
[0052] Finally, a combination of these advantageous properties is achieved for a solvent-free two-component adhesive composition.
[0053] -NCO component :
[0054] The MDI composition A1.C1 used for preparing A1 comprises at least 35% by weight of the 4,4'-isomer, based on its total weight, and preferably at least 45%.
[0055] Preferably, the composition has a 2,2' isomer content of less than 1 wt. %, based on its total weight.
[0056] According to one embodiment, the composition A1.C1 comprises at least 49% by weight of the 4,4' isomer, and preferably at least 49% by weight of the 2,4' isomer. Such compositions are commercially available. For example, mention may be made of Lupranat from Dow ® MIPI having a 4,4' isomer content of at least 49.5% by weight, a 2,4' isomer content of at least 49.3% by weight and a 2,2' isomer content of less than 0.2%. The percentage of -NCO groups expressed by weight of this product is equal to 33.5%.
[0057] According to another embodiment, the composition A1.C1 contains at least 95% by weight of the 4,4' isomer. Such compositions are also commercially available. For example, Isonate from Dow ® M125, whose 4,4' isomer content is at least 97% by weight and whose 2,2' isomer content is less than 0.1%. The percentage of -NCO groups (expressed on a weight / weight basis) of this product is equal to 33.6%.
[0058] Polyether diol PE used in polyol composition A1.C2 A 1 And polyether triol PE A 2 Preferably, the polyoxyalkylene glycols and triols are selected from polyoxyalkylene glycols, the linear or branched (saturated) alkylene moieties of which contain 2 to 4 carbon atoms, and preferably 2 to 3 carbon atoms. Therefore, most particularly preferably the respective functionality is 2 (for polyether glycol PE A 1 ) and 3 (for polyether triol PE A 2 ) of polypropylene glycol (PPG).
[0059] The above polyether diols and triols can be conventionally prepared and / or are widely commercially available. For example:
[0060] -Voranol ® 1010L, available from DOW CHEMICAL, is a polypropylene glycol (diol type) with a number average molecular weight between 984 and 1058 g / mol and a hydroxyl number of OHN between 106 and 114 mgKOH / g;
[0061] - Voranol® CP450, also available from DOW CHEMICAL, is a polypropylene glycol (triol type) with an average molecular weight of 425-455 g / mol and a hydroxyl number of 370-396 mgKOH / g;
[0062] The hydroxyl number of a polyol (expressed as OHN) denotes the number of hydroxyl functional groups per gram of polyol and is expressed in milliequivalents of potassium hydroxide (KOH) and is used for the quantitative determination of hydroxyl functional groups. OHN can be measured experimentally, for example, according to standard ISO 14900:2001.
[0063] According to a preferred variant, the polyol composition A1.C2 comprises a polyether PE A 1 and PE A 2 The amount corresponds to PE A 2 / (PE A 1 + PE A 2 ) with a weight / weight ratio of 18 to 24.
[0064] According to another preferred variant, the polyol composition A1.C2 consists of polyether diol PE A 1 And polyether triol PE A 2 composition.
[0065] The polyaddition between the MDI composition A1.C1 and the polyol composition A1.C2 is generally carried out at a temperature of 70 to 80° C. for 3 to 6 hours.
[0066] The amounts of Al.C1 and Al.C2 used in the polyaddition reaction should be such that the -NCO / -OH molar equivalent ratio is between 2.5 and 6.5. The term "-NCO / -OH molar equivalent ratio" is intended to mean the ratio of the number of equivalents of -NCO groups (present in Al.C1) to the number of equivalents of -OH groups (present in A2.C2). Preferably, the ratio is between 3.0 and 5.5, and even more preferably between 3.5 and 5.0.
[0067] Typically, the weight content of -NCO end groups of the polyurethane prepolymer A1 (expressed as the weight of said groups per 100 g of A1) varies within the range of 9-18%.
[0068] According to a first embodiment of the composition A, said composition consists essentially of the above-mentioned polyurethane prepolymer A1 as —NCO component. The term “essentially consisting of” is intended to mean that the A1 content of the composition A is at least 98% and may be as high as 100%.
[0069] According to a second embodiment of the composition A, in addition to the polyurethane prepolymer A1, the composition comprises an aliphatic polyisocyanate A2 whose -NCO terminal group functionality (expressed as the number of moles of -NCO functional groups per mole of A2) is in the range from 2 to 3.5 and whose NCO content is from 17 to 27% by weight, based on the weight of A2.
[0070] The term "aliphatic polyisocyanate" refers to a polyisocyanate whose -NCO terminal groups are directly attached to non-aromatic carbon atoms.
[0071] Aliphatic polyisocyanates A2 are preferably obtained by homocondensation or heterocondensation of aliphatic diisocyanate monomers, optionally with one or more compounds having mobile hydrogen, such as alcohols, diols, amines and other similar compounds. The term "homocondensation of diisocyanate monomers" refers to products obtained by polycondensation of diisocyanate monomers with themselves. The term "heterocondensation of diisocyanate monomers" refers to products obtained by polycondensation of at least two different diisocyanate monomers with each other, or by polycondensation of diisocyanate monomers with compounds having mobile hydrogen.
[0072] Even more preferably, the aliphatic polyisocyanate A2 has an allophanate functionality and is obtained by reacting at least one compound having a hydroxyl functionality with at least two diisocyanate monomers, usually in the presence of a specific catalyst, according to conventional methods well known to those skilled in the art. As shown in patent application WO 99 / 55756, the allophanate can advantageously be prepared directly from the isocyanate and the desired alcohol by heating in the presence of a catalyst of the dibutyltin dilaurate type.
[0073] The aliphatic polyisocyanate A2 is preferably obtained from at least one polyisocyanate and at least one monohydric alcohol, and preferably from a linear or branched alcohol comprising 1 to 20 carbon atoms.
[0074] Most particular preference is given to allophanates obtained from the homogeneous and / or heterogeneous polycondensation products of aliphatic isocyanate monomers, and most particularly of hexamethylene diisocyanate (or HDI) and / or HDI isocyanurate, also referred to as HDT (for hexamethylene diisocyanate trimer).
[0075] Among the commercially available products that can be used as aliphatic polyisocyanates A2, mention may be made of DESMODUR® XP 2860 from the company COVESTRO, which is an aliphatic polyisocyanate based on hexamethylene diisocyanate (HDI) and has allophanate functionality, an -NCO content of about 20% w / w and an -NCO terminal group functionality in the range from 2 to 3.5.
[0076] According to the second embodiment of the -NCO component, the content of A2 can vary within a range of up to 15% by weight, based on the total weight of the composition A. More preferably, based on the total weight of the composition A, the content of the polyurethane prepolymer A1 can then be from 83% to 98%, or from 85% to 100%, based on the total weight of the composition A.
[0077] Composition A is then typically prepared by mixing ingredients A1 and A2 under anhydrous conditions at a temperature of about 80°C.
[0078] Advantageously, the total content of -NCO groups expressed in % by weight is in the range from 13 to 18%, based on the total weight of composition A. This content can be calculated from the amount introduced in the preparation of composition A or can be measured by chemical titration using the reaction of dicyclohexylamine with the isocyanate functional groups and then quantitatively determining the excess amine using hydrochloric acid.
[0079] -OH component :
[0080] The -OH component is a composition B comprising a polyurethane prepolymer B1 containing at least two -OH end groups, obtained by a polyaddition reaction between a composition B1.C2 having a polyol with a functionality of 2 and a diphenylmethane diisocyanate (MDI) composition B1.C1. The latter composition comprises at least 35% by weight of the 4,4' isomer, the percentage being expressed based on the total weight of the composition.
[0081] Composition B1.C1 corresponds to the same definition as the above-mentioned composition A1.C1 and it is considered that when the two compositions B1.C1 and A1.C1 are used in a two-component adhesive composition according to the invention, they may be identical or different and may also comprise the same preferred embodiments as the latter composition.
[0082] Composition B1.C2 of polyols with a functionality of 2 comprises, based on the total weight of the composition:
[0083] - 38 to 42% by weight of a composition B1.C2.D comprising an aliphatic polyester diol PES having a molar mass Mn of 800 to 1200 g / mol B 1and partially aromatic polyester diols PES having a molar mass Mn of 1000 to 1400 g / mol B 2 , whose amount corresponds to PES B 1 / PES B 2 A weight / weight ratio between 0.35 and 0.45; and
[0084] -58 to 62% by weight of aliphatic polyether diols PE having a molar mass Mn of 350 to 550 g / mol B .
[0085] Aliphatic polyester diol PES B 1 and partially aromatic polyester diol PES B 2 Can be selected from:
[0086] - a polyester diol obtained by polycondensation of at least one dicarboxylic acid (or optionally one of its corresponding anhydrides or diesters) with at least one diol, or
[0087] - Polyester diols obtained by ring-opening polymerization of at least one cyclic lactone and at least one diol, for example polycaprolactone polyols.
[0088] The dicarboxylic acids that can be used for the synthesis of the abovementioned polyester diols are linear or branched, cyclic or acyclic, and saturated or unsaturated and preferably contain from 3 to 40 carbon atoms, and more preferably from 6 to 10 carbon atoms. The dicarboxylic acids are aliphatic or aromatic, depending on whether they are intended for the synthesis of aliphatic or partially aromatic polyester diols.
[0089] The diols which can be used for synthesizing the above polyester diols are selected from polyalkylene glycols, polyoxyalkylene glycols and mixtures of these compounds, the (saturated) alkylene moieties of these compounds being preferably linear or branched and preferably containing 2 to 40 carbon atoms, and more preferably 2 to 8 carbon atoms.
[0090] The cyclic lactones which can be used to synthesize the above polyester diols preferably contain 3 to 7 carbon atoms.
[0091] Aliphatic polyester diol PES B 1 Partially aromatic polyester diol PES B 2 They can be prepared by conventional methods and / or are widely commercially available. Thus, mention may be made of:
[0092] -Dekatol ®3008, which is an aliphatic polyester diol available from BOSTIK Corporation, having a number average molecular weight between 967 and 1039 g / mol and a hydroxyl number OHN between 108 and 116 mgKOH / g;
[0093] -Dekatol ® 1105, which is a partially aromatic polyester diol available from BOSTIK Corporation, has a number average molecular weight between 1069 and 1247 g / mol and a hydroxyl number OHN between 90 and 105 mgKOH / g.
[0094] According to a preferred variant, the composition B1.C2.D consists of a polyester diol PES B 1 and PES B 2 composition.
[0095] Composition B1.C2 also contains an aliphatic polyether diol PE having a molar mass Mn of 350 to 550 g / mol B The polyether is selected from polyoxyalkylene glycols, the (saturated) linear or branched alkylene moieties of which contain 2 to 4 carbon atoms, and more preferably 2 to 3 carbon atoms. Therefore, polypropylene glycols (PPG) each having a functionality of 2 are most particularly preferred.
[0096] Such polyether diols are widely commercially available. For example:
[0097] - Voranol from DOW CHEMICAL ® P400 is a polypropylene glycol diol with a number average molecular weight between 416 and 449 g / mol and a hydroxyl number OHN between 250 and 270 mgKOH / g.
[0098] According to a preferred variant, the composition B1.C2 is composed of the composition B1.C2.D and the polyether PE B composition.
[0099] The polyaddition reaction between the MDI composition B1.C1 and the polyol composition B1.C2 is generally carried out at a temperature of 70 to 80° C. for 3 to 6 hours.
[0100] The amounts of B1.C1 and B1.C2 used in the polyaddition reaction are such that the -NCO / -OH molar equivalent ratio is between 0.05 and 0.50, preferably between 0.1 and 0.4, and even more preferably between 0.2 and 0.3. The term "-NCO / -OH molar equivalent ratio" is intended to mean the ratio of the number of equivalents of -NCO groups (present in B1.C1) to the number of equivalents of -OH groups (present in B2.C2).
[0101] According to a preferred embodiment of composition B, said composition consists essentially of the above-mentioned polyurethane prepolymer B1 as -OH component. The term "essentially consists of" is intended to mean that the B1 content of composition B is at least 98% and may be as high as 100%.
[0102] Advantageously, the content of -OH groups expressed in % by weight, based on the total weight of composition B, is in the range from 3 to 5 % by weight.
[0103] This content can be estimated by calculating the weight of diol introduced by composition B1.C2, the weight of OHN of said diol and the weight of MDI.
[0104] This content can also be determined experimentally by simply measuring the OHN of composition B, in other words, by determining the amount of KOH (expressed in mg) required to neutralize the acetic acid formed after the reaction of excess acetic anhydride with 1 g of composition B.
[0105] Two-component adhesive composition:
[0106] In the two-component adhesive composition according to the present invention, the content of -NCO and -OH components is such that the -NCO / -OH molar equivalent ratio is in the range of 1.5 to 1.7. The term "-NCO / -OH molar equivalent ratio" refers to the ratio of the number of equivalents of -NCO groups (present in the -NCO component) to the number of equivalents of -OH groups (present in the -OH component).
[0107] The viscosity of each of the two -NCO and -OH components, measured at 23° C., is advantageously less than or equal to 25 Pa.s. The viscosity is also measured using a Brookfield viscometer in accordance with standard ISO 2555, published in 1999. Thus, each of the two components can conveniently be introduced into the laminator by means of a pump, they being in fact stored separately in containers of suitable capacity, for example 200 liter drums.
[0108] The mixing of the two components is carried out under hot conditions by the laminator operator in the ratios indicated at a temperature between 40 and 80°C (before starting).
[0109] Advantageously, the two-component adhesive composition thus obtained has a viscosity of 500-2000 mPa.s, preferably 500-1500 mPa.s, measured at 50° C. when mixed. The viscosity of the adhesive composition is therefore fully suitable for use in a laminating machine and for correct operation. The viscosity is measured using a Brookfield viscometer according to standard ISO 2555, published in 1999.
[0110] The two-component adhesive composition according to the invention may also contain additives which may be contained in the -NCO component and / or the -OH component, such as tackifiers (e.g. alkoxysilanes), rheological additives, catalysts or plasticizers. The total content of these optional additives in each of the -NCO and / or -OH components may be up to 2% by weight, based on the total weight of the components in question.
[0111] The two-component adhesive composition according to the invention is advantageously substantially free of solvents. These terms are intended to mean that the solvent content of the adhesive does not exceed 1% w / w, and preferably does not exceed 0.05%.
[0112] Multilayer film:
[0113] The invention also relates to a multilayer (or composite) film comprising two thin layers of material connected to one another by a continuous layer, characterised in that the layers consist of the two-component adhesive composition according to the invention in a crosslinked state in an amount of less than 10 g / m 2 .
[0114] According to one variant of the invention, the amount is less than or equal to 7 g / m 2 , and preferably in the range of 0.5 to 2.5 g / m 2 and even more preferably in the range of 1 to 2 g / m 2 within the range.
[0115] The material from which the thin layer surrounding the adhesive layer is made is typically selected from paper, metal (such as aluminum) or thermoplastic polymers (such as:
[0116] - Polyethylene (PE),
[0117] - Polypropylene (PP),
[0118] - copolymers based on ethylene and propylene,
[0119] - polyamide (PA), in particular biaxially oriented polyamide (or OPA or BOPA),
[0120] - Polyethylene terephthalate (PET), or
[0121] - ethylene-based copolymers, such as maleic anhydride-grafted copolymers, copolymers of ethylene with vinyl acetate (EVA), copolymers of ethylene with vinyl alcohol (EVOH) or copolymers of ethylene with alkyl acrylates, such as methyl acrylate (EMA) or butyl acrylate (EBA),
[0122] - Polystyrene (PS),
[0123] - Polyvinyl chloride (PVC),
[0124] - Polyvinylidene fluoride (PVDF),
[0125] - polymers or copolymers of lactic acid (PLA), or
[0126] -Polyhydroxyalkanoate (PHA).
[0127] The materials preferably chosen to constitute the thin layer surrounding the adhesive layer are PE, PP, PET and PA.
[0128] Mention may also be made of thin layers composed of thermoplastic polymers, preferably PE and PP, covered with a 1 μm monolayer of aluminum, aluminum oxide or silicon dioxide.
[0129] The thickness of the two thin layers adjacent to the adhesive layer used in the multilayer film of the present invention and the thickness of the other layers can vary in a wide range of 5 to 150 μm. The total thickness of the film can also vary in a wide range of from 20 to 400 μm.
[0130] The present invention also relates to a process for the continuous preparation of a multilayer film as defined above, comprising the following sequential steps:
[0131] (i) combining the -NCO and -OH components in the form of an adhesive mixture which is rendered flowable by heating at an appropriate temperature,
[0132] (ii) coating a thin layer of a first material in the form of a substantially continuous layer with said adhesive mixture,
[0133] (iii) laminating a second thin layer on the first thin layer applied according to step (i), and then
[0134] (iv) crosslinking the adhesive mixture.
[0135] Finally, the invention relates to the use of the multilayer film according to the invention in the production of flexible packaging. In particular, the composite film according to the invention can be used to produce a very wide variety of flexible packaging, which is formed by heat sealing (or heat welding) technology and then closed (after the step of packaging the product for the consumer).
[0136] The present invention will now be described in the following examples which are given by way of illustration only and should not be construed as limiting the scope of the invention.
[0137] Example 1 (reference) :-NCO component-Preparation of composition A consisting of polyurethane prepolymer A1
[0138] Under nitrogen flow and at ambient temperature, the following were placed in a closed 1-liter reactor equipped with a stirrer, heating device and temperature probe and connected to a vacuum pump: 19.12 g Lupranat ®MIPI, 220.74 g Voranol ® 1010L, 60.08 g Voranol ® CP450 and 0.08 g phosphoric acid (solution concentration 85%).
[0139] The amounts of these reagents correspond to a -NCO / -OH molar equivalent ratio equal to 4.94.
[0140] The mixture was then heated to 80° C. with mechanical stirring and maintained at this temperature for 4 hours, a reaction time which made it possible to achieve a weight content of NCO functions (monitored by potentiometric titration) of 17.5% (w / w).
[0141] Particular attention was paid to the temperature, which must not exceed 80° C. To this end, the polyol was added in portions (exotherm was checked between each addition of polyol).
[0142] Once the reaction is complete, the reaction medium is then cooled to 40° C. and maintained under a reduced pressure of 20 mbar in order to degas the mixture.
[0143] The weights of the agents / ingredients introduced relate to the total weight of composition A and are expressed in Table 1 as percentages.
[0144] The Brookfield viscosity at 23°C was measured and the values are listed in Table 1.
[0145] Example 2 (reference) :-NCO component-Preparation of composition A consisting of polyurethane prepolymer A1
[0146] Example 1 was repeated while varying the weights of the reagents to obtain a -NCO / -OH molar equivalent ratio of 3.67 (see Table 1).
[0147] Table 1 also lists the -NCO functional content and the Brookfield viscosity at 23° C. of the obtained polyurethane prepolymer A1.
[0148] Example 3 (reference): - NCO component - Preparation of composition A consisting of polyurethane prepolymer A1 and aliphatic polyisocyanate A2
[0149] Repeat Example 1, while using Isonate ® M125 replaces Lupranat ® MIPI and modify the weights of reagents to obtain the -NCO / -OH molar equivalent ratios shown in the table.
[0150] The -NCO functional content of the obtained polyurethane prepolymer A1 was 13.9% (shown in Table 1).
[0151] As soon as the -NCO functionality level of A1 has reached the indicated value, 80.00 g of DESMODUR® XP 2860 are introduced. The mixture is stirred for 1 hour at a temperature of 70 to 80° C. The reaction medium is then cooled to 40° C. and maintained under a reduced pressure of 20 mbar in order to deaerate the mixture.
[0152] The weight content of -NCO functional groups of composition A was 14.5% (w / w).
[0153] Example 4 (reference): Preparation of composition B consisting of -OH component - polyurethane prepolymer B1
[0154] Under nitrogen flow and at ambient temperature, the following substances were placed in a 1-liter closed reactor equipped with a stirrer, a heating device and a temperature probe and connected to a vacuum pump: 80.00 g Dekatol ® 3008, 208.00 g Dekatol ® 1105 and 432.00 g VORANOL ® P400. The mixture was then heated to 80°C with mechanical stirring and kept under reduced pressure of 20 mbar for 1 hour to dehydrate the polyol.
[0155] 80.00 g ISONATE® M125 were then introduced.
[0156] The amounts of these reagents correspond to a -NCO / -OH molar equivalent ratio equal to 0.25.
[0157] The mixture was kept at 80° C. for 4 hours, a reaction time which made it possible to achieve a total consumption of the NCO functions monitored by potentiometric titration.
[0158] Once the reaction is complete, the reaction medium is then cooled to 40° C. and maintained under a reduced pressure of 20 mbar in order to degas the mixture.
[0159] The amounts of agents / ingredients introduced relate to the total weight of composition B and are expressed in Table 2 as percentages.
[0160] The Brookfield viscosity at 23°C was measured and the values are listed in Table 2.
[0161] Table 2 also shows the -OH functional content of the polyurethane prepolymer B1 obtained and constituting composition B, and the Brookfield viscosity at 23° C. measured for composition B.
[0162] Example 5 (according to the invention): A two-component adhesive composition obtained by mixing the —NCO component of Example 1 and the —OH component of Example 4.
[0163] The -NCO component of Example 1 was mixed with the -OH component of Example 4 at a -NCO / -OH molar equivalent ratio equal to 1.65, which corresponds to a weight ratio of -NCO component / -OH component equal to 100 g -NCO component / 110 g -OH component.
[0164] Mixing was performed at a temperature of 50° C. in the laminator feed tank, and the Brookfield viscosity was measured at the same temperature immediately after mixing.
[0165] The corresponding data are shown in Table 3.
[0166] Examples 6 and 7 (according to the invention): Two-component adhesive compositions obtained by mixing the —NCO component of Example 2 (respectively Example 3) and the —OH component of Example 4.
[0167] Example 5 was repeated, replacing the -NCO component of Example 1 with the -NCO component of Example 2 (respectively Example 3).
[0168] The values of the -NCO / -OH molar equivalent ratio and the values of the -NCO component / -OH component weight ratio are shown in Table 3, and the Brookfield viscosity thereof was measured at 50°C.
[0169] Example 8 (according to the invention): Three-layer film with adhesive layer bonding oPA layer and PE layer:
[0170] The PA layer used a biaxially oriented polyamide film with a thickness of 15 µm, and the PE layer used a polyethylene film with a thickness of 50 µm.
[0171] The three-layer film was obtained by feeding the two-component adhesive composition of Example 5 into the tank of a Nordmeccanica-type laminator.
[0172] The laminator was provided with a coating device of role type having an open tank operating at a temperature of 50°C and a forward speed of 50 m / min. The thickness of the adhesive layer bonding the PA and PE layers was 2 g / m 2 .
[0173] Immediately after production, the three-layer film was stored under an environment of a temperature of 23° C. and a relative humidity (RH) of 50%.
[0174] The three-layer membrane was tested as follows:
[0175] A. Determination of cross-linking time:
[0176] A.1. Test Principle :
[0177] The purpose of this test is to measure the time (expressed in days) required for crosslinking of the constituent two-compound adhesives of the adhesive layers of a three-layer film, starting from the preparation of said film by lamination.
[0178] This time is evaluated by the number of days required for the film to have sufficient cohesion, and more specifically the number of days for which the cohesion of said film measured by the 180° peel test (described below) is greater than a reference value (reference value equal to 3 N / 15 mm).
[0179] A2. Membrane sampling :
[0180] Samples were taken from the three-layer film every day and kept under the storage conditions specified above at 23°C and 50% RH. The samples were subjected to a 180° peel test.
[0181] A.3.180° peel test instructions :
[0182] The 180° peel test is described in French standard NF T 54- 122. The principle of this test is to determine the force required to separate (or peel) 2 separate film layers bonded by a two-component adhesive.
[0183] A rectangular test specimen of 15 mm wide and about 10 cm long was cut out of the two-layer film. The two individual layers of the film included in the strip were manually separated from the ends of the specimen over a distance of about 2 cm, and the two free ends thus obtained were respectively connected to two fixtures, which were respectively connected to the fixed part and the movable part of the tensile test device located on a vertical axis.
[0184] The driving mechanism applies a uniform speed of 100 mm / min to the movable part, causing the two layers to separate. The separated ends of the two layers gradually move along the vertical axis to form an angle of 180°. The fixed part connected to the dynamometer measures the force borne by the held specimen, and the unit of force is N / 15 mm.
[0185] A.4. Results :
[0186] The cross-linking time was 2 days.
[0187] B. Determination of cohesion :
[0188] Samples were taken from the three-layer film and, after storage for 30 days, were kept under the above-specified storage conditions of 23° C. and 50% RH.
[0189] The sample was subjected to the 180° peel test described in A.3.
[0190] The cohesion is 6.55 N / 15 mm.
[0191] C. Determine the amount of primary aromatic amine (PAA) :
[0192] Samples were taken from the three-layer film and stored for 1 day and then for 2 days under the above-specified storage conditions of 23° C. and 50% RH.
[0193] The three-layer film thus sampled was formed into a 20 cm square bag by heat sealing at three locations, with one side left open. The bag was filled with 200 ml of an acetic acid aqueous solution (3 wt %).
[0194] The bag was then heat sealed and placed in an oven at 70°C for 2 hours.
[0195] The bag was then opened so that the aqueous solution could be extracted and analyzed.
[0196] After diazotization and reaction with N-naphthalene-1-ethylenediamine hydrochloride, PAA was quantified by UV spectroscopy at 550 nm and the color was concentrated on a solid phase chromatography column.
[0197] The results are expressed as milligrams of aniline per kilogram of aqueous acetic acid solution packed in the bag, and the unit is ppb.
[0198] After 1 day of storage of the three-layer membrane, the following results were obtained: 18 ppb.
[0199] After storing the three-layer film for 2 days, the following results were obtained: 3 ppb.
[0200] Examples 9 and 10 (according to the invention): Three-layer film with adhesive layer bonding oPA layer and PE layer:
[0201] Example 8 was repeated, replacing the two-component adhesive composition of Example 5 with Example 6 and Example 7, respectively.
[0202] The corresponding crosslinking time, cohesion and PAA amount of the three-layer films are listed in Table 3.
[0203] Example 11 (according to the invention): Three-layer film with an adhesive layer bonding the metallized PET layer and the PE layer:
[0204] First, a three-layer film was produced by repeating Example 8, except that the 15 μm thick biaxially oriented polyamide layer was replaced by a 9 μm thick layer consisting of PET metallized on the surface of the aluminum layer.
[0205] The cohesion of the three-layer film thus obtained was determined by repeating the test protocol of part B of example 8.
[0206] The cohesion is 1.74 N / 15 mm.
[0207] Examples 12 and 13 (according to the invention): Three-layer film with an adhesive layer bonding the metallized PET layer and the PE layer:
[0208] Example 11 was repeated, replacing the two-component adhesive composition of Example 5 with Example 6 and Example 7, respectively.
[0209] The cohesive force of the three-layer film thus obtained is shown in Table 3.
[0210] Table 1 - Composition A (-NCO component)
[0211] .
[0212] Table 2 - Composition B (-OH Component)
[0213] .
[0214] Table 3 - Two-component adhesive compositions
[0215] .
Claims
1. A two-component adhesive composition, which is a two-component polyurethane-based adhesive composition comprising an -NCO component and an -OH component such that: The NCO component is a composition A comprising a polyurethane prepolymer A1 having at least two -NCO terminal groups, A1 being obtained by a polyaddition reaction between: - a composition A1.C1 comprising at least 35% by weight of 4,4'-elastomeric diphenylmethane diisocyanate (MDI), said percentage being expressed based on the total weight of said composition, and - a polyol composition A1.C2 comprising a polyether diol PE having a molar mass Mn of 800 to 1200 g / mol A 1 and polyether triol PE with a molar mass Mn of 350 to 550 g / mol A 2 , whose amount corresponds to PE A 2 / (PE A 1 +PE A 2 ) in a weight / weight ratio of 15% to 30%, -A1.C1 and A1.C2 are used in an amount such that the -NCO / -OH molar equivalent ratio is between 2.5 and 6.5; The OH component is a composition B comprising a polyurethane prepolymer B1 having at least two -OH end groups, B1 being obtained by a polyaddition reaction between: a composition B1.C1 comprising at least 35% by weight of 4,4'-elastomeric diphenylmethane diisocyanate (MDI), said percentage being expressed based on the total weight of said composition, and - Composition B1.C2 of polyols with a functionality of 2, comprising, based on the total weight of the composition: 38 to 42% by weight of a composition B1.C2.D comprising an aliphatic polyester diol PES having a molar mass Mn of 800 to 1200 g / mol B 1 and partially aromatic polyester diols PES having a molar mass Mn of 1000 to 1400 g / mol B 2 , whose amount corresponds to PES B 1 / PES B 2 A weight / weight ratio between 0.35 and 0.45; and 58 to 62% by weight of aliphatic polyether diols PE having a molar mass Mn of 350 to 550 g / mol B ; -B1C1 and B1C2 are used in amounts such that the -NCO / -OH molar equivalent ratio is between 0.05 and 0.50; It is also provided that the amounts of the -NCO and -OH components of the two-component adhesive composition should be such that the -NCO / -OH molar equivalent ratio is in the range of 1.5 to 1.
7.
2. The two-component adhesive composition according to claim 1, characterized in that The MDI composition A1.C1 used for preparing A1 has a 2,2′-isomer content of less than 1% by weight, based on its total weight.
3. The two-component adhesive composition according to claim 1 or 2, characterized in that: The MDI composition A1.C1 comprises at least 49% by weight of the 4,4'-isomer.
4. The two-component adhesive composition according to claim 1 or 2, characterized in that: The polyether diol PE used in the polyol composition A1.C2 A 1 And polyether triol PE A 2 They are propylene glycols with functionality of 2 and 3 respectively.
5. The two-component adhesive composition according to claim 1 or 2, characterized in that: The -NCO end group content of the polyurethane prepolymer A1 is in the range of 9 to 18% by weight.
6. The two-component adhesive composition according to claim 1 or 2, characterized in that: The weight content of the polyurethane prepolymer A1 in the composition A as the -NCO component is at least 98%, based on the total weight of the composition A.
7. The two-component adhesive composition according to claim 1 or 2, characterized in that: Composition A also comprises, as -NCO component, an aliphatic polyisocyanate A2 having an -NCO terminal group functionality of 2 to 3.5 and an -NCO content of 17 to 27% by weight, based on the weight of A2.
8. The two-component adhesive composition according to claim 7, characterized in that The aliphatic polyisocyanate A2 carries an allophanate.
9. The two-component adhesive composition according to claim 1 or 2, characterized in that: The total -NCO group content expressed as wt % based on the total weight of composition A is 13 to 18%.
10. The two-component adhesive composition according to claim 1 or 2, characterized in that: The -OH group content expressed as wt %, based on the total weight of composition B, is 3 to 5%.
11. The two-component adhesive composition according to claim 1 or 2, characterized in that: Each of the two -NCO and -OH components has a viscosity less than or equal to 25 Pa.s measured at 23°C.
12. The two-component adhesive composition according to claim 1 or 2, characterized in that: When the two components are mixed, the viscosity measured at 50° C. is in the range of 500 to 2000 Pa.s.
13. A multilayer film comprising two thin layers of material connected to each other by a continuous layer, characterized in that The layer is composed of a two-component adhesive composition according to any one of claims 1 to 12, the two-component adhesive composition is in a cross-linked state, and the amount of the two-component adhesive composition is less than 10 g / m 2 .
14. A method for continuously preparing a multilayer film according to claim 13, comprising the following steps in sequence: (i) combining the -NCO and -OH components in the form of an adhesive mixture, rendering it flowable by heating at an appropriate temperature, (ii) coating a first thin layer of material in the form of a substantially continuous layer with the adhesive mixture, (iii) laminating a second thin layer on the first thin layer applied according to step (i), and then (iv) crosslinking the adhesive mixture.
15. Use of the multilayer film according to claim 13 for producing flexible packaging.
Citation Information
Patent Citations
Polyurethane lamination adhesive
US9458363B2
Method for preparing low viscosity tricondensate polyfunctional isocyanates
WO1999055756A1
Modified diphenylmethane diisocyanate-based adhesives
WO2012142148A1
Layered structures and articles prepared therefrom
WO2013043652A2
Ultralow monomer polyurethanes
WO2016142513A1